2-Deoxyglucose alleviates migraine-related behaviors by modulating microglial inflammatory factors in experimental model of migraine - Qiu, Tao; Zhou, Yanjie; Hu, Luyu; Shan, Zhengming; Zhang, Yu; Fang, Yuting; Huang, Wanbin; Zhang, Lily; Fan, Shanghua; Xiao, Zheman (Frontiers in Neurology, 2023)
Background: Targeting metabolic pathways has emerged as a new migraine treatment strategy as researchers realize the critical role metabolism plays in migraine. Activated inflammatory cells undergo metabolic reprogramming and rely on glycolysis to function. The objective of this study was to investigate the glycolysis changes in the experimental model of migraine and the role of glycolysis inhibitor 2-Deoxy-D-glucose (2-DG) in the pathophysiology of migraine. Methods: The experimental model of migraine was established by dural inflammatory soup (IS) perfusion. LPS-stimulated BV2 cells to establish an in vitro model. 2-DG was used to inhibit glycolysis. We explored the changes in glycolysis levels during inflammatory processes and effects of the glycolytic inhibitor 2-DG on mechanical allodynia, microglial activation, calcitonin-gene-related peptide (CGRP), c-Fos, brain-derived neurotrophic factor (BDNF) and inflammatory factor expression induced by inflammatory soup. Results: In the experimental model of migraine, key enzymes involved in glycolysis such as phosphofructokinase platelet (PFKP), hexokinase (HK2), hypoxia inducible factor-1α (HIF-1α), lactate dehydrogenase (LDH) and pyruvate kinase (PKM2) were expressed in the medullary dorsal horn. While the expression of COXIV decreased. There were no significant changes in glucose 6-phosphate dehydrogenase (G6PD), a key enzyme in the pentose phosphate pathway. The glycolysis inhibitor 2-DG alleviated migraine-like symptoms in an experimental model of migraine, reduced the release of proinflammatory cytokines caused by microglia activation, and decreased the expression of CGRP and c-Fos. Further experiments in vitro demonstrated that glycolysis inhibition can reduce the release of Iba-1/proBDNF/BDNF and inhibit the activation of microglia. Conclusion: The migraine rat model showed enhanced glycolysis. This study suggests that glycolytic inhibitor 2-DG is an effective strategy for alleviating migraine-like symptoms. Glycolysis inhibition may be a new target for migraine treatment.